Maintenance Crisis in Early Marriage: Socio-Legal Study on the Triggers of Divorce Lawsuits in Sukadana - Yustora, Denty; Arsyad, Mufid (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2024)
The maintenance crisis in early marriage in Sukadana shows that there are serious problems in family relations that have an impact on the increase in divorce lawsuits. Most previous studies have focused more on common factors of divorce such as the economy and household disharmony, while studies that specifically link the maintenance crisis in early marriage to a socio-legal perspective have been limited. This article analyzes how the husband's inability to fulfill alimony obligations transforms into a juridical reason in a divorce lawsuit and how these dynamics reflect the interaction between structural, cultural, and normative factors. This research uses a qualitative method with an exploratory-analytical design through a socio-legal approach. Data were obtained from in-depth interviews with six informants as well as an analysis of court decisions and related regulations. The results of the study show that the maintenance crisis is influenced by economic unpreparedness due to early marriage, low education, and weak internalization of family law norms. In addition, there is a shift in the meaning of alimony from a normative obligation to a structural burden and a change in power relations in the household that trigger conflicts. These findings confirm that divorce serves as a socio-legal mechanism to provide legal protection and certainty for women and reflects the need for a family justice model that is more responsive to social realities.